Enhanced Photothermal-Photodynamic Therapy by Indocyanine Green and Curcumin-Loaded Layered MoS2 Hollow Spheres via Inhibition of P-Glycoprotein - Li S (Dove Medical Press, 2021)
Shuai Li,1,* Shuping Yang,2,* Chong Liu,1 Jintong He,1 Tian Li,1 Changhui Fu,3 Xianwei Meng,3 Haibo Shao1 1Department of Interventional Radiology, The First Hospital of China Medical University, Shenyang 110001, Liaoning, People’s Republic of China; 2Department of Pain Medicine, The First Hospital of China Medical University, Shenyang 110001, Liaoning, People’s Republic of China; 3Laboratory of Controllable Preparation and Application of Nanomaterials, Chinese Academy of Sciences Key Laboratory of Cryogenics, Technical Institute of Physics and Chemistry, Chinese Academy of Sciences, Beijing 100190, People’s Republic of China*These authors contributed equally to this workCorrespondence: Haibo Shao Department of Interventional RadiologyThe First Hospital of China Medical University, Shenyang 110001, Liaoning, People’s Republic of ChinaEmail haiboshao@aliyun.comXianwei MengLaboratory of Controllable Preparation and Application of Nanomaterials, Chinese Academy of Sciences Key Laboratory of Cryogenics, Technical Institute of Physics and Chemistry, Chinese Academy of Sciences, Beijing 100190, People’s Republic of ChinaEmail mengxw@mail.ipc.ac.cnPurpose: P-glycoprotein (P-gp), which is highly expressed in liver cancer cells, is one of the obstacles for the treatment of cancer. In this study, we have prepared and characterized a kind of novel ICG&Cur@MoS2 (ICG and Cur represent indocyanine green and curcumin, respectively) nanoplatform, which can achieve photothermal-photodynamic therapy and inhibit the P-gp effectively and safely.Methods: In this work, plenty of studies including drug release, acute toxicity, Western blot, real-time PCR, cell viability, therapeutic experiment in vivo, immunofluorescence and so on were conducted to test the antitumor potential of ICG&Cur@MoS2 and the inhibitory effect of curcumin on P-gp.Results: The ICG&Cur@MoS2 NPs exhibit an excellent photothermal effect and relatively low toxicity. Cell viability in the ICG&Cur@MoS2 + NIR group was significantly lower than that in ICG@MoS2 + NIR group (75.3% vs 81.2%, 59.0% vs 64.4%, 20.3% vs 27.5%, and 15.4% vs 22.3%) at the concentration of ICG at 0.5, 5, 25, 50 μg/mL (P< 0.05 at each concentration). Western blot, Q-PCR, and immunofluorescence assay indicate ICG&Cur@MoS2 NPs can inhibit the P-gp effectively and safely. In vivo, the tumors in the ICG@MoS2 + NIR group are significantly smaller than those in the MoS2 + NIR group (95.0 vs 420.9 mm3, p< 0.05).Conclusion: In conclusion, we have successfully synthesized ICG&Cur@MoS2 nanoparticles which can not only achieve PTT-PDT but also inhibit P-gp effectively. Our findings indicate that the PTT-PDT exhibits great potential in the treatment of hepatocellular carcinoma. Meanwhile, ICG&Cur@MoS2 can effectively inhibit the expression of P-gp, which will enhance the PDT effect.Keywords: P-glycoprotein, hepatocellular carcinoma, indocyanine green, curcumin, MoS2, photothermal-photodynamic therapy